Monoscopic photogrammetry to obtain 3D models by a mobile device: a method for making facial prostheses - Salazar-Gamarra, Rodrigo [UNESP]; Seelaus, Rosemary; Lopes da Silva, Jorge Vicente; Silva, Airton Moreira da; Dib, Luciano Lauria [UNESP] (Biomed Central Ltd, 2016)
Purpose: The aim of this study is to present the development of a new technique to obtain 3D models using photogrammetry by a mobile device and free software, as a method for making digital facial impressions of patients with maxillofacial defects for the final purpose of 3D printing of facial prostheses. Methods: With the use of a mobile device, free software and a photo capture protocol, 2D captures of the anatomy of a patient with a facial defect were transformed into a 3D model. The resultant digital models were evaluated for visual and technical integrity. The technical process and resultant models were described and analyzed for technical and clinical usability. Results: Generating 3D models to make digital face impressions was possible by the use of photogrammetry with photos taken by a mobile device. The facial anatomy of the patient was reproduced by a *.3dp and a *.stl file with no major irregularities. 3D printing was possible. Conclusions: An alternative method for capturing facial anatomy is possible using a mobile device for the purpose of obtaining and designing 3D models for facial rehabilitation. Further studies must be realized to compare 3D modeling among different techniques and systems. Clinical implication: Free software and low cost equipment could be a feasible solution to obtain 3D models for making digital face impressions for maxillofacial prostheses, improving access for clinical centers that do not have high cost technology considered as a prior acquisition.
Keywords: 123D Catch; 3D photography; Maxillofacial rehabilitation; Facial prosthetics; Photogrammetry; Oral rehabilitation